Penerapan Tindak Pidana Pencucian Uang (Money Laundering) Dalam Transaksi Perbankan - Abd. Manab (JURNAL RECHTENS, 2025)
The purpose of this study is to analyze and find the application of money laundering crimes in banking transactions. Using a qualitative research method through a normative juridical approach, namely an approach using a positivist juridical conception, namely that law is identical to written norms made by the authorities. That must pay attention to three legal elements, namely: Substance, Subject, and Culture. These three elements have been considered by the Indonesian government in enforcing the law in Indonesia and applied to the Crime of Money Laundering, the Crime of Money Laundering in Banking transactions. This quite important role can be seen starting from the formation of a Special Working Unit before the effectiveness of the PPATK in supervising TPPU in Indonesia to the issuance of OJK regulations regarding the KYC (Knowing Your Customer) system and requiring every PJK Bank to implement the system as an effort to prevent TPPU in the banking sector.